2020
DOI: 10.1063/5.0014278
|View full text |Cite
|
Sign up to set email alerts
|

Improvements to the Faraday cup fast ion loss detector and magnetohydrodynamic induced fast ion loss measurements in Joint European Torus plasmas

Abstract: Upgrades to electronic hardware and detector design have been made to the JET thin-foil Faraday cup fast ion loss detector [Darrow et al., Rev. Sci. Instrum. 75, 3566 (2004)] in anticipation of the upcoming deuterium–tritium (DT) campaign. An improved foil stack design has been implemented, which greatly reduces the number of foil-to-foil shorts, and triaxial cabling has mitigated ambient noise pickup. Initial tests of 200 kHz digitizers, as opposed to the original 5 kHz digitizers, have provided enhanced anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…This is consistent with the results presented in figure 3 and the evolving neutron rate which is dominated by beam-thermal interactions [33]. Analysis of Faraday cup fast ion loss array [21] signals, which are sensitive to fusion product and RF-heated beam losses, did not reveal any sawtooth induced losses above the detector noise floor. These loss measurements suggest that the sawtooth may only induce weak losses and be more likely to redistribute the fast ion population.…”
Section: Sawtooth Induced Transportsupporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with the results presented in figure 3 and the evolving neutron rate which is dominated by beam-thermal interactions [33]. Analysis of Faraday cup fast ion loss array [21] signals, which are sensitive to fusion product and RF-heated beam losses, did not reveal any sawtooth induced losses above the detector noise floor. These loss measurements suggest that the sawtooth may only induce weak losses and be more likely to redistribute the fast ion population.…”
Section: Sawtooth Induced Transportsupporting
confidence: 90%
“…The two instabilities provide the means for both resonant and non-resonant transport for analysis. Discussed extensively in reference [6], the saturated kink modes give rise to measureable fast ion losses in JET's Faraday cup fast ion loss detector [21] and scintillator probe [22].…”
Section: Experimental Scenariomentioning
confidence: 99%
“…In short, the deeper the ion deposition, the higher the energy. Reference [22] provides a complete table of the resolvable energy range per foil per ion species.…”
Section: Jet's Faraday Cup Fast Ion Loss Detector Arraymentioning
confidence: 99%
“…Synthetic loss detectors have been produced to compare numerically modeled losses to experimental measurements [14][15][16][17][18]. It has been readily observed that fast ion loss detector (FILD) signals correlate with many loss mechanisms of interest [19][20][21][22][23]. Thus, it is possible to form a fully integrated energetic particle transport model which can then be quantitatively corroborated against experimental measurement.…”
Section: Introductionmentioning
confidence: 99%
“…The TRANSP/NUBEAM code provides a time-dependent model for the equilibrium and fast ion distribution for use in the ORBIT-kick model, which calculates the fast ion transport associated with a supplied EP instability. Furthermore, the geometry for a series of thin-foil Faraday cup fast ion loss detectors, capable of spatial and energy-resolved loss measurements [74] was installed in the code to produce synthetic loss signals for comparison to the experiment. Perturbatively induced losses can then be tracked to the detector geometry to produce synthetic loss signals.…”
Section: Ep Transport and Lossesmentioning
confidence: 99%